Dynamic evolution and numerical analysis of rock deformation under impact failure based on corner correlation method - Zhou, Xingui; Ye, Zhongbao; Miao, Hong; Li, Wei; Wang, Xueru; Li, Chenfeng (Frontiers in Earth Science, 2023)
To fulfill the requirement for deformation measurement within the failure area during rock failure, a newly developed digital image algorithm, known as the corner correlation method, was implemented. A corner correlation measure-ment system was established by utilizing a Split Hopkinson Pressure Bar (SHPB) and a high-speed camera. The study focused on monitoring the deformation and failure characteristics of sandstone samples under dynamic loading. Specifically, the initiation, extension, and contraction processes of surface cracks on sandstone were examined. Parameters such as crack width, width propagation rate, and extension shrinkage rate were measured. The entire crack development process was analyzed, including crack width, crack initiation point, crack extension and con-traction trajectory, elongation and contraction velocity, width expansion rate, and longitudinal crack penetration, which were obtained at any given time on the surface of the rock sample. Additionally, the attenuation law of stress, characterized by an exponential decay of the stress peak value, was discussed through numerical simulation using a similar model.